A comparative study on magnetocaloric effect in NdRu2Si2 and NdRu2Ge2. (2020) - Sharma, Sanjay; Singh, Rashmi; Kumar Maurya, Gyanendra; Singh, Ankit; Ahmad, Faizan; Tiwari, Akhilesh; Kumar, Pramod
Abstract: Temperature dependent magnetization, M-H isotherm and MCE properties of NdR u 2 G e 2 and NdR u 2 S i 2 have been studied to make a comparison between these two compounds. Both of these take two magnetic transitions, one at T N and another at T t . T t of both is same, i.e. 10 K but T N of NdR u 2 G e 2 is 19 K while that of NdR u 2 S i 2 is 23.5 K. They both show interesting M-H isotherms. The values of entropy change ( Δ S M ) for NdR u 2 G e 2 and NdR u 2 S i 2 are 3.2 J kg −1 K −1 and 4 J kg −1 K −1, at a field of 50 kOe wide temperature range. The value of Δ S M of NdR u 2 G e 2 is smaller than that of NdR u 2 S i 2 as the field dependent magnetization isotherm does not lead to saturation at 50 kOe in NdR u 2 G e 2 but it is approaching to saturation in case of NdR u 2 S i 2 .